Root Canal Stripping: Malpractice or Common Procedural Accident—An Ethical Dilemma in Endodontics - Ionela Elisabeta Ciobanu; Darian Rusu; Stefan-Ioan Stratul; Andreea Cristina Didilescu; Corina Marilena Cristache (Case Reports in Dentistry)
Root canal stripping is defined as an oblong, vertical perforation that appears especially in the middle section of curved root canals during endodontic treatments with nickel-titanium (Ni-Ti) instruments. Its occurrence may drastically affect the outcome of the treatment, transforming a common otherwise efficient endodontic procedure into a complication such as tooth extraction. In order to discuss the ethical and legal consequences, two cases of dental strip perforations are herewith presented. Due to the existence of risk factors for dental strip perforation, experience of the clinician and the use of magnification and modern imagistic methods (CBCT) may avoid or reduce the frequency of this type of accidents. Under correct working circumstances, dental stripping should not be regarded as a malpractice but as a procedural accident. However, the patient must always be informed, before and during the endodontic procedure, about the event and the possible complications that may occur.